Micropropagation and determination of essential oil components and antimicrobial activities of temu hitam (Curcuma aeruginosa roxb.) - Abdul Aziz, Julia (2015)
Curcuma aeruginosa Roxb. which belongs to the family Zingiberaceae is one of the oriental herbs that is gaining popularity for its medicinal properties as tonic called ‘Jamu’. This species contains potential essential oils that have promising market potential with antimicrobial properties useful for food preservation, cosmetics and pharmaceutical treatment. The major constraints in the cultivation of C. aeruginosa are the low rate of propagation, has a period of dormancy, commercially exploited and poor flowering and seed set. Vegetative propagation through underground rhizomes often results in fungal disease that can influence the quality and quantity of essential oils within the plants. Thus, in vitro propagation is an alternative to accelerate plant multiplication for large scale production of true-to-type disease-free plants. The rhizome buds were tested on Murashige and Skoog medium containing BAP, Kin and TDZ at 0, 1,2, 4, 6, 8 and 10mg/l respectively. Shoot induction was achieved after 12 weeks of culture with a maximum of 2.55 shoots on MS medium containing 1 mg/l TDZ. The excised shoots were subcultured on MS medium containing 1 mg/l TDZ with different concentrations of NAA (0, 0.1, 0.5, 1, and 2 mg/l). The shoot multiplication rate was further enhanced to 7.55 shoots on MS medium supplemented with 1 mg/l TDZ and 2 mg/l NAA after 8 weeks of culture. Rooting was tested on IBA, IAA and NAA at 0.1, 0.5, 1, 2 and 4 mg/l. Optimum rooting (26.33 roots) was obtained in MS medium containing 0.1 mg/l IAA. Well rooted shoots were acclimatized on sand, peat, soil, peat : soil (1:1), peat :sand (1:1), sand : soil (1:1) and peat : soil : sand (1:1:1). The highest plantlet survival (89%) was in mixture of peat : soil : sand (1:1:1). The essential oils and chemical composition of both field grown plants and in vitro grown plantlets of C. aeruginosa were investigated. For the field grown plant, the optimum oil yield was produced from dried rhizomes 0.63% (v/w) followed by dried leaves 0.46% (v/w), fresh rhizomes 0.26% (v/w) and fresh leaves 0.20% (v/w). The major constituents of fresh leaves oil was curzerene and germacrone (5.16% and 4.91% respectively) while dried leaves, fresh and dried rhizomes were dominated by 1,8-cineole at 17.21%, 20.53% and 18.41% and dextro-camphor at 6.55%, 6.08% and 9.89% respectively. In vitro grown plantlets were divided into two parts (fresh shoots and roots). The yield obtained was 0.066% (v/w) for fresh roots and fresh shoots at 0.046% (v/w). The main group compounds in the fresh shoots oil were L-camphor (10.91%) and 1,8-cineole (6.51%) while fresh roots oil was dominated by methyl elaidate (8.99%) and methyl hexadecanoate (6.79%). The effectiveness of essential oil from different vegetative parts of C. aeruginosa field grown plant was tested on microorganisms. The oils from fresh leaves, dried leaves, fresh rhizomes and dried rhizomes exhibited moderate antibacterial activity against Gram positive bacteria Staphylococcus aureus, Bacillus subtillis and Gram negative bacteria Eschericia coli ranging from 7.00 to 10.00 mm. Moderate activities was also shown against two selected fungi Aspergillus niger and Candida albicans ranging from 7.00 – 9.66 mm zone of inhibition. Minimum inhibitory concentration (MIC) value to effectively inhibit the microbial activity was 0.00625 mg/μl except S. aureus which showed MIC at 0.0125 mg/μl. All the four extracted oils appeared to be inactive on Gram negative bacteria Serratia marcescens. From this study, the successful in vitro propagation of C.aeruginosa could provide large scale production of disease-free planting materials. For essential oil production, the dried rhizome of field grown C.aeruginosa plants were recommended as they produced more essential oil compared to leaves. Both dried and fresh rhizomes have potential as antimicrobial agent since they were dominated by 1,8-cineole and dextrocamphor which were reported to possess potent antimicrobial activity.